2011
DOI: 10.1055/s-0040-1703514
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Total Antioxidant Content of Saliva on Dental Caries.

Abstract: Objective: The aim of the study was to evaluate the Total Antioxidant level in saliva of caries patients with and without smoking habit. Methods: A total of 80 individuals were included in the study. Unstimulated saliva was colleced. Samples of smoking and non smoking caries patients showing only Streptococcus mutans growth were analysed for Total Antioxidant level and smokers and nonsmokeres without any caries were considered as control groups. Caries isolates were confirmed as Streptococcus mutans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The anti-oxidants present in the saliva are the first defense mechanism against oxidative stress due to free radicals ( Hegde et al, 2012 ; Shetty et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-oxidants present in the saliva are the first defense mechanism against oxidative stress due to free radicals ( Hegde et al, 2012 ; Shetty et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Hegde et al . [ 18 ] and Shetty et al ,[ 21 ] the increase in salivary TAC levels is due to an increase in the suspension of proteins and cariogenic activity. Levels of antioxidants alter in response to an infection or disease.…”
Section: Discussionmentioning
confidence: 99%
“…Majority (48.3%) of them were in the age group of 20-35 years due to the reason that in the last ten years, so many new dental colleges have been established in India. 14 Various studies have shown the role of antioxidants in the caries prevention, and a study done by Shetty et al 15 who reported that free radicals in tobacco smoke increase the prevalence of dental caries. Motamayal et al 16 revealed that there are association between Total Antioxidant Capacity of saliva and dental caries and this may be helpful in caries prevention.…”
Section: Discussionmentioning
confidence: 99%